Deregulation Policies in Theory, Privatization in Practice: A Case of Nigerian Universities - Adetunji, Adeniyi Temitope (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2016)
This paper is designed to study deregulation policy as it has been applied to the university sector in Nigeria. Previous study suggests that the Nigerian government introduced deregulation to universities, among others policies. The government aims to use the policy to change the situation or address problems Nigerian university are confronting, but it is very difficult to conclude whether the assumption of deregulation is correct. Therefore, this study maps deregulation policy from past literature to give a clear picture of how the policy has been perceived within the system. This study is desk research and is done to verify the existing knowledge of the policy within the sector. The findings reveal that the sector only witnesses deregulation as a general policy not as expected in practice, because the government still jealously guide and take responsibility for the universities they establish, without giving room to private investors to participate in the business.